2019
DOI: 10.1093/europace/euz155
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cryoballoon or radiofrequency ablation in symptomatic paroxysmal or persistent atrial fibrillation

Abstract: Aims To evaluate the effectiveness and safety of cryoballoon ablation (CBA) compared with radiofrequency ablation (RFA) for symptomatic paroxysmal or drug-refractory persistent atrial fibrillation (AF). Methods and results Prospective cluster cohort study in experienced CBA and RFA centres. Primary endpoint was ‘atrial arrhythmia recurrence’, secondary endpoints were as follows: procedural results, safety, and clinical course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 24 publications
14
100
1
Order By: Relevance
“…The overall comparability of these two different techniques, after being addressed by the FIRE and ICE trial, 19 was recently confirmed by an observational cluster cohort study by Hoffmann et al, 23 who showed no difference between CB-A and RF ablation in terms of atrial arrhythmia recurrence and, furthermore, significantly less rehospitalization due to re-ablations and adverse events during follow-up after CB-A.…”
Section: Discussionmentioning
confidence: 91%
“…The overall comparability of these two different techniques, after being addressed by the FIRE and ICE trial, 19 was recently confirmed by an observational cluster cohort study by Hoffmann et al, 23 who showed no difference between CB-A and RF ablation in terms of atrial arrhythmia recurrence and, furthermore, significantly less rehospitalization due to re-ablations and adverse events during follow-up after CB-A.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the current analysis for repeat ablation revealed a possibly significant superiority of CBA over RFA after the sensitivity analysis accounted for heterogeneity. In the persistent AF subanalysis of the FREEZE Cohort Study, 19 repeat ablation was nearly halved with CBA as the persistent AF subanalysis including over 1000 patients showed a consistent and much higher (approximately 65%) success rate between the CBA and RFA groups. However, the duration of persistent AF history in this cohort study was less than 1 year, which is shorter than the duration of more than 2 years in most studies included in this meta -analysis.…”
Section: What's New?mentioning
confidence: 97%
“…In the recent FREEZE Cohort Study, 19 in which a second-or third -generation cryoballoon was used in 76% of patients undergoing CBA, a conference abstract 14 (FIGURE1). Two conference abstracts were excluded due to a suspicion of overlapping population.…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis that included 3,527 patients with PaAF and PeAF showed that the recurrence rates after CBA or RFCA was similar [7]. A prospective cluster cohort study that involved 4,189 patients showed that the recurrence rate of PeAF did not differ between CBA and RFCA during middle-term follow up [8]. A single-center large-scale study also found that the free survival rate for atrial arrhythmias was 78.6% after a single procedure for PaAF and 72.3% for PeAF at a median 39 months follow-up [9].…”
Section: Introductionmentioning
confidence: 99%